2009
DOI: 10.4049/jimmunol.182.2.860
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Expression of A20 Markedly Increases the Efficacy of Double-Stranded RNA-Activated Dendritic Cells As an Anti-Cancer Vaccine

Abstract: A20 is a zinc finger protein with ubiquitin-modifying activity. A20 has been described as negatively regulating signaling induced by the TNF receptor and TLR family in a number of cell types, including mouse bone marrow-derived dendritic cells (DCs). However, the expression and effect of A20 in activated human monocyte-derived DCs have not been previously evaluated. We report that DCs activated with the TLR3 ligand poly(I:C) up-regulate A20. Down-regulating A20 demonstrated its role in the functional activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 59 publications
4
53
0
Order By: Relevance
“…A20-deficient macrophages display prolonged NF-κB activity (27,28), and A20-silenced DCs induce robust antitumor immune responses to reject engrafted tumors in immunized mice (34). Recently, Breckpot et al reported that A20-silenced human DCs had an enhanced capacity to polarize the IFN-γ-producing CD4 + T cell response and to prime the tumor-specific CD8 + T cell response (35). These results indicate that A20 plays a critical role in controlling immunostimulatory potency of APCs.…”
Section: Introductionmentioning
confidence: 99%
“…A20-deficient macrophages display prolonged NF-κB activity (27,28), and A20-silenced DCs induce robust antitumor immune responses to reject engrafted tumors in immunized mice (34). Recently, Breckpot et al reported that A20-silenced human DCs had an enhanced capacity to polarize the IFN-γ-producing CD4 + T cell response and to prime the tumor-specific CD8 + T cell response (35). These results indicate that A20 plays a critical role in controlling immunostimulatory potency of APCs.…”
Section: Introductionmentioning
confidence: 99%
“…Lentivectors have successfully delivered to DCs short hairpin RNAs (shRNAs) targeting A20. The abrogation of A20 expression caused DC maturation, effective CD8 cell responses and inihibition of regulatory T cells (Tregs) [55,56].…”
Section: Control Of DC Maturation By Expression Of Molecular Activatomentioning
confidence: 99%
“…Therefore, A20 down-regulation could result in prolonged NF-κB activation, resulting in DCs with enhanced stimulatory capacity. LV delivered A20-targeted shRNA (Song et al 2008) and direct introduction of siRNA (Breckpot et al 2009) were applied to down-regulate A20 in mouse and human DCs, respectively. These approaches showed that A20 controls DC maturation, cytokine production and immunostimulatory potency.…”
Section: Engineering Lentiviral Vectors To Enhance the Immune Stimulamentioning
confidence: 99%
“…Human DCs with down-regulated A20 expression had an increased NF-κB activity and showed enhanced and sustained IL-10 and IL-12 secretion. These DCs were more potent in stimulating Melan-A CTL responses (Breckpot et al 2009). …”
Section: Engineering Lentiviral Vectors To Enhance the Immune Stimulamentioning
confidence: 99%